2020
DOI: 10.12688/f1000research.20144.2
|View full text |Cite
|
Sign up to set email alerts
|

Willingness-to-pay for a hypothetical Ebola vaccine in Indonesia: A cross-sectional study in Aceh

Abstract: Background: Some Ebola vaccines have been developed and tested in phase III clinical trials. However, assessment of whether public have willingness to purchase or not, especially in unaffected areas, is lacking. The aim of this study was to determine willingness to pay (WTP) for a hypothetical Ebola vaccine in Indonesia. Methods: A cross-sectional study was conducted from 1 August to 30 December 2015 in five cities in Aceh province of Indonesia. Patients’ family members who visited outpatient departments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
(3 reference statements)
0
9
1
Order By: Relevance
“…Our findings revealed a higher proportion of WTP and a lower proportion of unwilling mothers to pay for the vaccines to their children (93.1% vs. 3.0%) than the corresponding values (88% vs. 55%) reported from a study in Nigeria [26]. Besides, the mean WTP value in our study is lower than that reported for a hypothetical vaccine in Malaysia [27] and higher than the mean value (US$ 2.08) reported for the Ebola vaccine elsewhere [28]. The WTP of mothers for the Human Papillomavirus vaccine to their daughters (US$ 208) [29] was more than 48 times the mothers' mean WTP value (US$ 4.3) for the vaccines to their children in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Our findings revealed a higher proportion of WTP and a lower proportion of unwilling mothers to pay for the vaccines to their children (93.1% vs. 3.0%) than the corresponding values (88% vs. 55%) reported from a study in Nigeria [26]. Besides, the mean WTP value in our study is lower than that reported for a hypothetical vaccine in Malaysia [27] and higher than the mean value (US$ 2.08) reported for the Ebola vaccine elsewhere [28]. The WTP of mothers for the Human Papillomavirus vaccine to their daughters (US$ 208) [29] was more than 48 times the mothers' mean WTP value (US$ 4.3) for the vaccines to their children in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Indonesia is a middle-income country with relatively low vaccine coverage and high vaccine hesitancy ( 18 20 ). Some studies have been conducted to assess acceptance on new vaccines against emerging and re-emerging infectious diseases in southeast Asia, such as for dengue ( 21 25 ), Zika ( 26 ), and Ebola ( 27 ). No study has been conducted on COVID-19 vaccine acceptance in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Published by Elsevier Inc. to pay (WTP) studies, can help governments and care providers to consider different factors such as socioeconomic class and healthcare service quality to implement an affordable and effective health system for patients. 21,22 Different studies were conducted to estimate WTP for a hypothetical dengue vaccine in Malaysia 23 and Southeast Asia Region 24 and cholera vaccine and Ebola vaccine in Bangladesh 25 and Indonesia, 26 respectively. Taking into consideration the enormous amount of money spent to create a vaccine and the commercial background of most of the companies working on the vaccine, many studies were conducted to test peoples' WTP for the COVID-19 hypothetical vaccine such as in Chile, 27 Romania, 28 Indonesia, 29 Malaysia, 30 United Arab Emirates, 31 Ecuador, 32 and the United States.…”
Section: Introductionmentioning
confidence: 99%